English Language: English Language - Pradana, Aryo Wibi (English Education Department Slamet Riyadi University Surakarta, 2024)
The study aimed to find out the influence of Quizizz as a learning media towards student learning motivation in English learning among tenth grade students at MAN 1 Surakarta during the 2023/2024 academic year. A quantitative method was used with a One Group PretestPosttest design, with 26 students selected through random sampling method. Data was collected through pre-test, post-test, and questionnaire. The researcher used a paired sample t-test formula and SPSS 16 application to analyze the data. The results showed a significant influence of Quizizz on student motivation in English learning. The t-test resulted in a tcount value of 37,787, which was greater than the ttable at a 5% significance level of 2,060. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The study highlights the importance of using Quizizz as a learning media for English learning among tenth grade students. Keywords: Quizizz, Learning Media, Learning Motivation, Learning English.